Efeito do cobre na população de bactérias e fungos do solo, associação ectomicorrízica e no desenvolvimento de mudas de eucalipto e canafístula - Santos, Lílian Castilho dos (2006)
The microrganisms are sensitive to the presence of determined concentrations of copper being considered biorremediadores able to move metal through active and passive processes, accumulating them in his cellular compartments The aim of this study was to evaluate the effects of copper on the soil bacteria and fungi population and ectomycorrhizal association, as well as on the growth of eucalyptus (Eucalyptus grandis W. Hill ex Maiden) and canafístula (Peltophorum dubium (Sprengel) Taubert) seedlings. The soil samples were collected in reject, adjacent, eucalyptus cultivation, pinus with 2 and 10 year old area, in the Camaquã Minas, Caçapava, Rio Grande do Sul, Brazil. The counting of bacteria and fungi soil population was carried out in the laboratory in culture medium, incubated 8 days, to 25 ºC. Subsequently, experiment was installed to determine the copper level effect (0, 100, 200, 300 mg kg-1 of Cu) on eucalyptus and canafistula seedlings, inoculated or not with the Pisolithus microcarpus (Cooke & Massee) Cunn. UFSC Pt 116. It was determine the height, stem diameter, aerial fresh matter and root dry matter, and ectomycorrhizal colonization percentage, at 110 days. The highest average for the total bacteria population was found in the adjacent and eucalyptus cultivation area, for the soil fungi population was in the adjacent area. The copper quantity of 203 mg dm-3 inhibits the bacteria and fungi soil population. The inoculation of the seedlings of eucalyptus and canafístula with P. microcarpus UFSC Pt 116 increase the development of aerial fresh matter and height of seedlings. The results show that the canafístula is able to form ectomycorrhizal association with P. microcarpus UFSC Pt 116 (4,96 %). The development of eucalyptus and canafístula seedlings were inhibited by the copper level even inoculated with P. microcarpus UFSC Pt 116. The population of bacteria and fungi in the soil as well as the seedlings of eucalyptus and canafístula are straightly influenced by the copper level in the soil, being favoured by the inoculation with P. microcarpus UFSC Pt 116.